The Influence of Shopee’s Shopping Convenience - Hening Lintang Kinanthi; Ratna Roostika (Jambura Science of Management, 2023)
This study aims to analyze the influence of online shopping convenience on consumer satisfaction and the effect of consumer satisfaction on behavioral intentions and E-WOM. This study uses a quantitative method and the method used is the Structural Equation Model with AMOS 24.0 software. This research used 235 respondents which was conducted on Indonesian citizens who use Shopee. The variable Convenience of Online Shopping has a positive and significant effect on consumer satisfaction. The consumer satisfaction variable also has a positive and significant effect on consumer behavioral intentions and E-WOM.